2019
DOI: 10.21608/ejabf.2019.53997
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations of zooplankton community in Lake Edku, Egypt

Abstract: Lake Edku receives huge amounts of waste waters discharged from various effluents that could be affecting on its ecological and biological features. Samples were collected seasonally for seven subsequent years (2009-2015) from 9 stations represent the different habitats in Lake Edku to assess the ecological status of the lake through long-term variations of zooplankton community. The data of physico-chemical parameters indicated that some parameters had wide variations in yearly average and others changed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Water properties are considered the key driving factors for abundant microalgae in lakes and water canals. Temperature and salinity are the main factors in controlling species distribution and abundance (Zakaria and El-Naggar 2019). Tavsanoglu et al (2015) showed that the changes in salinity will have a substantial impact on aquatic ecosystems, where it can result in osmotic stress on cells, uptake or loss of ions, and effects on the cellular ionic ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Water properties are considered the key driving factors for abundant microalgae in lakes and water canals. Temperature and salinity are the main factors in controlling species distribution and abundance (Zakaria and El-Naggar 2019). Tavsanoglu et al (2015) showed that the changes in salinity will have a substantial impact on aquatic ecosystems, where it can result in osmotic stress on cells, uptake or loss of ions, and effects on the cellular ionic ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, over‐collection of commercial molluscs reduces the number of certain species or may even result in the complete disappearance of other species from the area (Gössling et al, 2004). Anthropogenic activities (especially the salts as results of desalination processes) strongly affect the concentration of nutrient, nitrification, in the marine ecosystem (especially N and P), which was considered an important key for plankton nutritional value and communities (El‐Naggar et al, 2019; Zakaria & El‐Naggar, 2019), which is reflected on aquatic food webs (El‐Damhougy et al, 2019; Zakaria et al, 2018b). Finally, the integration of remote sensing technique with macrobenthic invertebrate distribution data revealed that anthropogenic activities affect the presence and absence of species and influence the dominance status of species in the stations.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced technologies like satellite imaging and remote sensing have made it easier to assess anthropogenic activities and the threat of human impact on marine resources (El‐Kafrawy et al, 2020). Satellite imagery has immensely helped mapping of coastal ecosystems and provided estimates of the extent and nature of land cover alteration in the coastal ecosystem (Zakaria et al, 2019; Zakaria & El‐Naggar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of Brachionus spp. is important indicator of the status of aquatic ecosystem (Zakaria & El-Naggar, 2019). During 7 years of study period, seven Brachionus species were recorded in Lake Mariout.…”
Section: Discussionmentioning
confidence: 99%